Better cowpeas - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1986)
Improved varieties of cowpea developed by the International Institute for Tropical Agriculture (IITA) and planted in Niger, yielded three times more than local varieties despite receiving only half the normal rainfall. According to the IITA, 33 new...